The ethics of categorization in sport: An analysis of the possible elimination of under 19 lightweight owing in Canada - Giesbrecht, J. A. (Faculty of Applied Health Sciences, Brock University St. Catharines, 2020)
In 2017a proposed rule changewas made by a working group appointed by Rowing Canada Aviron to eliminate the U19 lightweight rowing category in Canada. While this proposal did not come to fruition, it did raise questions about the purpose and ethics of maintaining such a category. The purpose of this study was therefore to explore the perceptions of those closely involved with U19 lightweight rowing in Canada and the ethical considerations and ramifications of a possible banon this category. Ten interviews were conducted with coaches and administrators closely associated with the topic to ascertain individual and group perceptions of this proposal. Based on Charles Taylor`s hermeneutic phenomenology, this study uncovered and evaluated the ethical implications and validity of the possible elimination of U19 rowing in Canada and provided a commentary on categorization in sport more broadly. The results of the interviews revealed six main emergent themes that included concepts of natural lightweights, opportunity and fairness, health and harm reduction, education, coaching abuse or neglect, and accountability. After analyzing the perceptions of participants and applying an ethical analysis to the issue, a possible ban of U19 lightweight rowing in Canada was deemed ethically unjustifiable.